The effect of Cadmium, Copper, and Lead on Brassica juncea in Hydroponic Growth Medium - Lê, Thị Thanh Trân (2024)
This study measured the accumulation of cadmium (Cd), lead (Pb), and copper (Cu) in Brassica juncea grown using the hydroponic method in a water environment contaminated with these heavy metals. The accumulated metal content in each part of the plant was monitored after one, three, and six weeks of exposure. The concentrations of Cd, Cu, and Pb in the biomass of B. juncea were determined using atomic absorption spectroscopy. The results showed that heavy metal pollution in water caused heavy metal accumulation in vegetable biomass. Pb tended to accumulate lower vegetable biomass than Cu and Cd. The metal accumulation level in Cu and Cd was in the order of roots > stems > leaves, while with Pb, the concentration accumulated in roots > leaves > stems. The translocation factors of Cu, Cd, and Pb from shoots to stems and shoots to leaves were less than 1